Conditioned media derived from mesenchymal stem cell cultures: The next generation for regenerative medicine. (20th March 2019) - Gunawardena, Tarini Nawamalie Abeysinghe; Rahman, Mohammad Tariqur; Abdullah, Basri Johan Jeet; Abu Kasim, Noor Hayaty
Abstract: Recent studies suggest that the main driving force behind the therapeutic activity observed in mesenchymal stem cells (MSCs) are the paracrine factors secreted by these cells. These biomolecules also trigger antiapoptotic events to prevent further degeneration of the diseased organ through paracrine signalling mechanisms. In comparison with the normal physiological conditions, an increased paracrine gradient is observed within the peripheral system of diseased organs that enhances the migration of tissue‐specific MSCs towards the site of infection or injury to promote healing. Thus, upon administration of conditioned media derived from mesenchymal stem cell cultures (MSC‐CM) could contribute in maintaining the increased paracrine factor gradient between the diseased organ and the stem cell niche in order to speed up the process of recovery. Based on the principle of the paracrine signalling mechanism, MSC‐CM, also referred as the secretome of the MSCs, is a rich source of the paracrine factors and are being studied extensively for a wide range of regenerative therapies such as myocardial infarction, stroke, bone regeneration, hair growth, and wound healing. This article highlights the current technological applications and advances of MSC‐CM with the aim to appraise its future potential as a regenerative therapeutic agent.